Strategy Increasing Performance Employee: Analysis Implementation Knowledge Management, Career Development, Team Work & Employee Engagement - Wenny Desty Febrian; Nuraeni; Didin Sjarifudin; Bekti Setiadi; Supardi (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this research is to find gaps between variables from previous research and to find relationships between variables, to improve employee performance which is supported by several main factors. This study uses a literature review study to review several variables whose articles have been published in international journals, the findings of this study are that there are variables that are significant to the dependent variable and some are not significant, the framework created can be said to be novel because there has never been any research with the framework created by the research team.